2013
DOI: 10.1016/j.cell.2013.02.033
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis Nucleosome Remodeler DDM1 Allows DNA Methyltransferases to Access H1-Containing Heterochromatin

Abstract: Summary Nucleosome remodelers of the DDM1/Lsh family are required for DNA methylation of transposable elements, but the reason for this is unknown. How DDM1 interacts with other methylation pathways, such as small RNA-directed DNA methylation (RdDM), which is thought to mediate asymmetric methylation through DRM enzymes, is also unclear. Here, we show that most asymmetric methylation is facilitated by DDM1 and mediated by the methyltransferase CMT2 separately from RdDM. We find that heterochromatic sequences p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

76
1,328
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 951 publications
(1,476 citation statements)
references
References 59 publications
76
1,328
6
Order By: Relevance
“…In contrast, H1.1 and H1.2 were previously found to prevent the access of DNA methyltransferases to DNA. 30 Thus, this work supports the crucial role played by H1.3 in facilitating chromatin accessibility in response to particular environmental signals. 31 Epigenetic processes and changes in response to drought stress were also approached during this conference.…”
Section: Microscopy Molecules and Modeling: Elucidating Nuclear Orgsupporting
confidence: 56%
“…In contrast, H1.1 and H1.2 were previously found to prevent the access of DNA methyltransferases to DNA. 30 Thus, this work supports the crucial role played by H1.3 in facilitating chromatin accessibility in response to particular environmental signals. 31 Epigenetic processes and changes in response to drought stress were also approached during this conference.…”
Section: Microscopy Molecules and Modeling: Elucidating Nuclear Orgsupporting
confidence: 56%
“…The Arabidopsis methylome is established by distinct DNA methyltransferases, each with a preference for one of three cytosine contexts CG, CHG, and CHH (Law and Jacobsen, 2010;Zemach et al, 2013). Comparing the CG, CHG, and CHH content in the motifs ( Figure 7D) to the methylation sensitivities revealed three general rules: (1) TFs with strong CG or CHG in their motifs were strongly inhibited in both mC-all and mCG-only regions, (2) TFs with only CHH in their PWM were generally insensitive to methylation, and (3) motifs containing multiple cytosine contexts typically showed very high methylation inhibition.…”
Section: The Epicistromementioning
confidence: 99%
“…Generally, CG methylation is generated by the conserved DNA methyltransferase METHYLTRANSFERASE1 (MET1; Vongs et al, 1993;Genger et al, 1999;Kankel et al, 2003;Law and Jacobsen, 2010) and CHG methylation is produced by the plant-specific DNA methyltransferase CHROMO-METHYLASE3 (CMT3; Cao and Jacobsen, 2002a;Law and Jacobsen, 2010;Zemach et al, 2010b), whereas CHH de novo methylation is established by a 24-nucleotide small interfering RNA (siRNA) directed DNA methylation (RdDM) pathway to guide the DNA methyltransferases DOMAINS REARRANGED METHYLTRANSFERASE1 (DRM1) and DRM2 in plants (Cao and Jacobsen, 2002b;Law and Jacobsen, 2010;Mosher and Melnyk, 2010). Also, several studies have demonstrated that de novo CHH methylation could be established by the plant-specific DNA methyltransferase CMT2 in an independent RdDM pathway (Zemach et al, 2013;Stroud et al, 2014). In addition, the DNA methyltransferase-like Dnmt2, first identified from bacteria, also was detected in plants, although its function in regulating DNA methylation remained largely unknown (Hermann et al, 2003;Mund et al, 2004;Ponger and Li, 2005).…”
mentioning
confidence: 99%